Student’s Error Analysis in Solving The TIMSS (Trends in International Mathematics and Science Study) of Number Content With Fong’s Schematic Model for Error Analysis - Eni Rahayu (Jurnal Pendidikan Matematika, 2018)
This research is a qualitative descriptive research that aims to find out student’s errors and the cause of errors in solving the TIMSS problem of number content and reasoning cognitive. The subject of this reseach are students of class VIII.C SMP Srijaya Negara with 26 students. Data collection techniques in this research are tests and interviews. Analysis of test and interview data follows Fong's Schematic Model for Error Analysis. The result of the research are student’s error consist of language errors, operational errors, and mathematical themes errors, but student’s errors are more dominant in operational error. The factors that cause student’s error are (a) the lack of students accuracy in reading problem or in process of calculation, (b) in hurry in solving the problems, c) the lack of mastery of material students, (d) students are not accustomed to write information known and asked on question, (e) students are not accustomed to correcting answers before being collected.